Association of post-COVID-19 fatigue with mental health problems and sociodemographic risk factors. Issue 4 (2nd October 2021) - Uygur, Omer Faruk; Uygur, Hilal
ABSTRACT: Purpose: : Our objective was to obtain an initial prevalence estimate of post-COVID-19 fatigue in Turkey and identify psychological and sociodemographic risk factors associated with post-COVID-19 fatigue. Materials and methods: : The data were collected from a cross-sectional community-based survey among the population recovered from COVID-19 in Turkey. A sociodemographic data form, the Fatigue Assessment Scale (FAS), and the Depression Anxiety Stress Scale-21 (DASS-21) were included in the survey. Participants were divided into two groups, fatigued and non-fatigued, based on their FAS scores. Sociodemographic and psychological characteristics of the two groups were examined with comparative analyses, and binary regression analysis identified predictors of post-COVID-19 fatigue. Results: : The completed survey ( N = 275) included individuals from 50 cities in Turkey who reported a prior COVID-19 illness. The mean age was 34.67 ± 8.35 years and 58.2% were female. Significant fatigue was detected in 56.4% (155) of participants. Female gender, history of psychiatric illness, history of psychiatric drug use, and current psychiatric drug use were significantly higher in the fatigued group than in the non-fatigued group ( p < 0.01). In addition, the fatigued group showed significantly higher scores on all domains of the FAS and DASS-21 scales than the non-fatigued group ( p < 0.01). Female gender and a high DASS-21 total score were predictors of post-COVID-19 fatigue. Conclusion: : Patients with post-COVID-19 fatigue should be evaluated for mental health issues.